Resistomycin Induced Apoptosis and Cycle Arrest in Human Hepatocellular Carcinoma Cells by Activating p38 MAPK Pathway In Vitro and In Vivo - Zhuo Han; Xingming Zhao; E Zhang; Jiahui Ma; Hao Zhang; Jianjiang Li; Weidong Xie; Xia Li (MDPI AG, 2021)
Resistomycin, a quinone-related natural antibiotic, has shown strong inhibitory activity against human hepatocellular carcinoma (HCC) in vitro. Here, we investigated the role of p38 MAPK in the pro-apoptotic and G2/M phase arrest action of HCC HepG2 cells upon treatment with resistomycin in vitro and in vivo. Our results showed that resistomycin dose- and time-dependently reduced the viability of HepG2 cells and also showed lower cytotoxicity in normal human kidney cells (293T) and hepatocyte cells (HL-7702). Resistomycin treatment induced apoptosis and cell cycle arrest in HepG2 cells, accompanied by changes in the expression of related proteins, including Bax, Cyclin B1, etc. Surprisingly, resistomycin-mediated apoptotic cell death and cell cycle arrest were impeded by SB203580 (an inhibitor of p38 catalytic activity), suggesting that p38 MAPK signaling may play an important role that impedes eventual cell death. In this connection, data in vitro and in vivo demonstrated that resistomycin increased the phosphorylation of p38 and MAPKAPK-2 in HepG2 cells. Furthermore, we provided evidence that p38 signaling is involved in resistomycin-induced p38 MAPK pathway effects in HCC, using computer docking models. Our study indicated that resistomycin activates the p38 MAPK signaling pathway by which the growth of HepG2 cells is suppressed for apoptosis and G2/M phase arrest in vitro and in vivo, and it is a promising therapeutic leading compound for drug development in HCC treatment.